2019
DOI: 10.1002/aoc.4695
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of microwave‐assisted biologically active triazole silanes

Abstract: The alliance of new drug, green technology and public health initiatives is essential for the ecosystem. The microwave technique is used to synthesize new drugs cognate to metronidazole. A new family of triethoxysilanes (3a–3e) was synthesized after reconnaissance with terminal alkynes (2a–2e) as an array using the Huisgen 1,3‐dipolar cycloaddition. All products were obtained in excellent yield with recovery of the catalyst as well as the solvent, and in a short time span. The design feature of these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition, 3‐aminopropylsilatranes and their derivatives show antimicrobial, [ 12,13 ] antiparasitic, [ 14 ] antihepatitis B, [ 15 ] antitumor, [ 16 ] immunomodulatory [ 17 ] and growth stimulating [ 18 ] activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 3‐aminopropylsilatranes and their derivatives show antimicrobial, [ 12,13 ] antiparasitic, [ 14 ] antihepatitis B, [ 15 ] antitumor, [ 16 ] immunomodulatory [ 17 ] and growth stimulating [ 18 ] activity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27,28 ] The MG approach is based on the principle “two heads are better than one”, which has been successfully employed to create novel hybrid compounds with anticancer, anti‐inflammatory, antimicrobial, and other activities. [ 12–14,29–33 ]…”
Section: Introductionmentioning
confidence: 99%
“…The diverse biological significance attached with these N‐heterocyclic fragments is the motivation behind pursuing our research in this area. Because of the presence of the azomethine linkage, Schiff bases particularly those of nitrogen and oxygen containing heterocycles, play a pivotal role in drug chemistry because they display a wide range of activities such as anti‐cancer, antitumor, antibacterial, antioxidant, antifungal, anti‐viral, antiparasitic, anti‐inflammatory, anti‐HIV and herbicidal [9–18] …”
Section: Introductionmentioning
confidence: 99%
“…Because of the presence of the azomethine linkage, Schiff bases particularly those of nitrogen and oxygen containing heterocycles, play a pivotal role in drug chemistry because they display a wide range of activities such as anti-cancer, antitumor, antibacterial, antioxidant, antifungal, anti-viral, antiparasitic, anti-inflammatory, anti-HIV and herbicidal. [9][10][11][12][13][14][15][16][17][18] Another important genre of pharmacophore that have recently attracted the interest of medicinal chemists is Silatranes, caged compounds constituting a transannular dative bond between silicon and nitrogen. [19] Current revelation by our group has shown that nitrogen heterocycles like morpholine, piperidine and pyrrolidine linked with silatranyl fragments are promising drug candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation